Selective Ion Exchange in Supramolecular Channels in the Crystalline State. Issue 13 (30th January 2019) - Ichihashi, Katsuya; Konno, Daisuke; Maryunina, Kseniya Yu.; Inoue, Katsuya; Toyoda, Kazuhiro; Kawaguchi, Shogo; Kubota, Yoshiki; Tatewaki, Yoko; Akutagawa, Tomoyuki; Nakamura, Takayoshi; Nishihara, Sadafumi
Abstract: Artificial ion channels are of increasing interest because of potential applications in biomimetics, for example, for realizing selective ion permeability through the transport and/or exchange of selected ions. However, selective ion transport and/or exchange in the crystalline state is rare, and to the best of our knowledge, such a process has not been successfully combined with changes in the physical properties of a material. Herein, by soaking single crystals of Li2 ([18]crown‐6)3 [Ni(dmit)2 ]2 (H2 O)4 (1 ) in an aqueous solution containing K +, we succeeded in complete ion exchange of the Li + ions in 1 with K + ions in the solution, while maintaining the crystalline state of the material. This ion exchange with K + was selectively conducted even in mixed solutions containing K + as well as Na + /Li + . Furthermore, remarkable changes in the physical properties of 1 resulted from the ion exchange. Our finding enables not only the realization of selective ion permeability but also the development of highly sensitive biosensors and futuristic ion exchange agents, for example. Abstract : Upon soaking a single crystal composed of crown ether based ion channels and [Ni(dmit)2 ] − units in a K + ‐containing aqueous solution, the Li + ions in the crystal were completely and selectively exchanged with K + ions from the solution while the crystalline state of the material was maintained. The ion exchange induced remarkable changes in the magnetic properties and ionic conductivity.